2003
DOI: 10.1016/s0925-4773(03)00177-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of neurabin II as a novel doublecortin interacting protein

Abstract: The neuronal migration protein doublecortin (DCX) that associates with microtubules through a tandem DCX repeat, is required for the development of the complex architecture of the human cerebral cortex. Using a yeast two-hybrid screen with Dcx as bait, we have isolated neurabin II/spinophilin, an F-actin binding protein known to play a role in dendritic spine formation. The coiled-coil domain of neurabin II binds to a DCX region encompassing the C-terminal portion of the second DCX repeat and the N-terminal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 39 publications
5
49
0
Order By: Relevance
“…Nevertheless, some results implicated an interaction of DCX with the actin cytoskeleton, directly or via Neurabin 2. 19,20 Interestingly, BAC26042 and, to some extent the DCX domains of DCLK2 localized to the cell periphery, at sites reminiscent of lamellipodia (Fig. 5E-H and Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Nevertheless, some results implicated an interaction of DCX with the actin cytoskeleton, directly or via Neurabin 2. 19,20 Interestingly, BAC26042 and, to some extent the DCX domains of DCLK2 localized to the cell periphery, at sites reminiscent of lamellipodia (Fig. 5E-H and Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, although neurabin 2 regulates the interaction of DCX with actin, DCX has the capability of directly interacting with actin and affecting its polymerization. 19,20 It is possible that additional DCX proteins interact directly with actin, alternatively additional mediators and regulators may exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doublecortin (DCX) is a microtubule-associated protein that can induce microtubule polymerization and stabilize microtubules filaments. Immunoprecipitation experiments with brain extracts showed that Spn and DCX interact incultured cells (Tsukada et al, 2003). In vitro assays showed that DCX also binds to and bundles F-actin, suggesting that the protein crosslinks microtubules and F-actin.…”
Section: -The Spinophilin Interactomementioning
confidence: 99%
“…Thus, an emerging notion is that Spn and neurabin 1 may differentially affect their target proteins and perform quite distinctive function in cell. Morphological studies have established that Spn is enriched at plasma membrane of cells although the protein is also expressed widely throughout the cytoplasm (Smith et al, 1999;Richman et al, 2001;Tsukada et al, 2003). Spn, which is expressed partly in the nucleus in mammalian cells, interacts in vitro and in vivo with the tumor-suppressor ARF (Alternative Reading Frame).…”
Section: -Introductionmentioning
confidence: 99%